2021
DOI: 10.3389/fonc.2021.578928
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Down of Mucolipin 1 Channel Promotes Tumor Progression and Invasion in Human Glioblastoma Cell Lines

Abstract: Among cancers that affect the central nervous system, glioblastoma is the most common. Given the negative prognostic significance of transient receptor potential mucolipin 1 (TRPML1) channel reduction in patients with glioblastoma, as discussed in previous publications, the aim of the current study was to investigate the biological advantage of TRPML1 loss for glioma cells. Human glioblastoma primary cancer cells (FSL and FCL) and glioblastoma cell lines (T98 and U251) were used for that purpose. TRPML1 silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The pRB protein shows high susceptibility to cytosolic proteases, with CatB-like proteolytic activity [ 44 ]; moreover, we and other researchers [ 43 , 66 ], have previously reported that TRPML1 knock-down results in the leak of mature lysosomal CatB. In this regard, increased levels of mature CatB were evidenced in the cytosol fraction of siTRPML2 T98 cells, but not U251 cells compared with siGLO control cells.…”
Section: Discussionmentioning
confidence: 77%
“…The pRB protein shows high susceptibility to cytosolic proteases, with CatB-like proteolytic activity [ 44 ]; moreover, we and other researchers [ 43 , 66 ], have previously reported that TRPML1 knock-down results in the leak of mature lysosomal CatB. In this regard, increased levels of mature CatB were evidenced in the cytosol fraction of siTRPML2 T98 cells, but not U251 cells compared with siGLO control cells.…”
Section: Discussionmentioning
confidence: 77%
“…GBM cell lines T98 and U251 (grade IV) were obtained as previously described. 49 Cells were grown until 80% of confluence in Eagle’s minimum essential medium (EMEM, Sigma, Merck Life Science S.r.l. Milano, Italy) plus 10% heat-inactivated fetal calf serum (HIFCS, Life Technologies, Monza, Italy), penicillin (100 U/mL), and streptomycin (50 ÎŒg/mL) in a humidified atmosphere of 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The impairment of the function of TRPML1 leads to enlarged lysosomes, lysosomal calcium accumulation, and increased pH, which further contributes to lysosomal malfunction and cellular senescence 119 , 126 . It has been reported that mitochondrial ROS can activate TRPML1, inducing lysosomal calcium release 85 , further inducing autophagy and lysosomal biogenesis 127 and delaying cellular senescence. However, excess ROS levels in the mitochondria have the opposite effect, leading to lysosomal dysfunction and cellular senescence 126 , 127 .…”
Section: The Role Of Organelle Interaction In Cellular Senescencementioning
confidence: 99%
“…It has been reported that mitochondrial ROS can activate TRPML1, inducing lysosomal calcium release 85 , further inducing autophagy and lysosomal biogenesis 127 and delaying cellular senescence. However, excess ROS levels in the mitochondria have the opposite effect, leading to lysosomal dysfunction and cellular senescence 126 , 127 .…”
Section: The Role Of Organelle Interaction In Cellular Senescencementioning
confidence: 99%